2016
DOI: 10.1128/iai.00657-16
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis TRP32 Is a Nucleomodulin That Directly Regulates Expression of Host Genes Governing Differentiation and Proliferation

Abstract: Ehrlichia chaffeensis is an obligately intracellular bacterium that reprograms the mononuclear phagocyte through diverse effector-host interactions to modulate numerous host cell processes, including transcription. In a previous study, we reported that E. chaffeensis TRP32, a type 1 secreted effector, interacts with multiple host nucleus-associated proteins and also autoactivates reporter gene expression in yeast. In this study, we demonstrate that TRP32 is a nucleomodulin that binds host DNA and alters host g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 63 publications
(55 reference statements)
1
40
0
Order By: Relevance
“…Neither of these phenotypes were due to accumulation of undegraded cellular protein as treatment with the proteasome inhibitor bortezomib did not alter cellular localization of TRP32 (Figure 4B ). In order to test this possibility, we performed a cellular assay using a firefly luciferase reporter expressed under control of the TRP32 target promoters in the presence or absence of these inhibitors (Farris et al, 2016 ). We found that Pyr41 caused drastic decreases in expression of both the constitutively transcribed Renilla luciferase and the firefly luciferase suggesting that this inhibitor broadly dysregulated transcription (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither of these phenotypes were due to accumulation of undegraded cellular protein as treatment with the proteasome inhibitor bortezomib did not alter cellular localization of TRP32 (Figure 4B ). In order to test this possibility, we performed a cellular assay using a firefly luciferase reporter expressed under control of the TRP32 target promoters in the presence or absence of these inhibitors (Farris et al, 2016 ). We found that Pyr41 caused drastic decreases in expression of both the constitutively transcribed Renilla luciferase and the firefly luciferase suggesting that this inhibitor broadly dysregulated transcription (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…TRP32 also binds a G-rich motif consisting of imperfect GGTGGC-like sequence repeats, but preferentially targets genes regulating cell proliferation and differentiation. TRP32 was also shown to activate and repress expression of targets in a gene-specific manner during infection and in a luciferase reporter assay (Luo and McBride, 2012 ; Farris et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations support the hypothesis of large-scale transcriptional alteration induced by Ank200 via mechanisms associated with the regulation of Alu-Sx elements. TRP32 and TRP120 bind to host-cell DNA at G-rich and G + C-rich motifs, respectively, as well as chromatin-associated proteins, such as histone methylases and demethylases, polycomb-group (PcG) proteins and other components of chromatin-remodeling complexes [43][44][45][46][47][48]. TRP120 acts as a transcriptional activator for host genes [44], while TRP32 activates or represses expression of its target genes [46,47].…”
Section: Ankyrin Repeat-and Tandem Repeat-containing Nucleomodulins: mentioning
confidence: 99%
“…Ehrlichia TRP32 is regulated by different modifications. Tyrosine phosphorylation controls its nuclear localization [47], while ubiquitination on lysine 63, catalyzed by the host cell protein NEDD4L, is required for TRP32 transcription factor function and subnuclear localization [111]. For TRP120, ubiquitination and sumoylation are critical in establishing its eukaryotic target landscape and thus, function [51,52].…”
Section: Regulation Of Nucleomodulins By Ptmsmentioning
confidence: 99%